Analisis Pelaksanaan Kegiatan Operasi Bantuan Logistik Di Wilayah Papua Barat - Adiguna, Ilham; Syuroh, Mat; Sandy, Amiruddin (@-Publik: Jurnal Administrasi Publik, 2024)
This research aims to determine the analysis of the implementation of logistics assistance operations in the West Papua region. The research method used is a qualitative method with data analysis techniques, data collection, data condensation, data display, conclusion drawing/verification. The object of this research was the Badminton Task Force in West Papua, totaling 7 informants who conducted interviews. Problem identification in this research discusses the defense equipment used in implementing logistical assistance, unpredictable weather factors, and the operational terrain traversed. The results of the research carried out show that the implementation of logistics assistance activities in West Papua has shown good results, runs in accordance with existing procedures, and all logistics activities to meet needs are running quite well and are supported by TNI Headquarters. TNI Headquarters will support the needs of goods and services for troops during operational duties.